Improved analytical method for pile response due to foundation pit excavation. (July 2020) - Liu, Jianwen; Shi, Chenghua; Cao, Chengyong; Lei, Mingfeng; Wang, Zuxian
Abstract: Owing to the rapid growth of urban population and fast developments of urbanization, new pit excavations are inevitably conducted in close proximity to existing structures, which will cause additional displacement and internal force to piles in turn adversely impact the surrounding structures. Thus, it's a major challenge to reasonably predict the pile response to new excavations. Previous analytical methods generally ultimate Euler–Bernoulli beam with Winkler found to consider the pile–soil interactions and treat the foundation as homogeneous and continuous, while the shearing effect of the pile, excavation–induced disturbance to the pile surrounding soil and the inherent properties of the natural multi–layered strata are neglected. This study develops an improved analytical solution to evaluate the effects of adjacent excavations on a pile. The pile–soil interaction is simulated using a Timoshenko beam resting on a Vlazov foundation and the explicit solutions are derived using the finite differential method, based on which the pile shear characteristics and inhomogeneity of multilayer soils are further considered. The proposed method is tested against a numerical analysis and a field case study, the maximum errors of the predicted and simulated pile deflections are 4.5% and 1.8% under different excavation depth, respectively, predictions given by the proposed method show good agreements with the numerical results and the field measurements. Further discussions are performed to investigate the applicability of the proposed method from three aspects, including foundation models, shear characteristics of piles and inhomogeneity of soils. The discussions indicate that the proposed method is robust and able to be applied to most engineering projects.